Enhancing Innovation and Technological Capabilities in the Management of E-Waste: Case Study of South African Government Sector. (July 2017) - Bob, Urmilla; Padayachee, Anshu; Gordon, Mark; Moutlana, Irene
E-Waste is one of the fastest growing waste streams globally. In the South African context e-Waste is receiving considerable attention from the Department of Environmental Affairs (DEA) who view it as being one of the fastest growing and most complex waste streams. There is recognition that e-Waste provides both threats and opportunities. In terms of the latter, e-Waste if well-managed can address the triple challenges of job creation, poverty and inequality as well as promote environmental sustainability that aligns to the South African government's mandate to protect the rights of all its citizens to an environment that is not harmful to health and well-being. The article presents and discusses primary data collected from a survey-based and case study research (including key informant interviews) with representatives from various government departments and agencies. The findings reveal that there are substantial variations within the government sector in terms of who is responsible for e-Waste, the amount of e-Waste generated, policies and procedures that are in place, and how e-Waste is managed. The results show that government departments and agencies have stockpiles of e-Waste and there is substantial storing/hoarding of e-Waste throughout the country. Furthermore, current practices of managing e-Waste are unsustainable and undesirable. Based on the findings and literature review undertaken which includes an overview of the e-Waste challenge and trends globally and in South Africa specifically, a model for the management of e-Waste in the government sector that drives broader economic revitalisation and sustainability imperatives is proposed that embraces a regional approach.